(untitled) (Andamios, Revista de Investigación Social, 2011)
The article is an approach to a concept of alterity as irreducible and constituent of identity, stating a critical point of view from the modern concept of subject. The presence of the other in oneself is evidence of the impossibility of closure of subjectivity. We work on two short stories -”There are more things” (Borges) and “How I met Superman” (Chesterton)- which show a non-representable figure of “otherness”. By questioning the pair “human / non-human”, these stories make the concept of human being as an universal show its contingency. Such figures of alterity also challenge narrative forms by showing the limits of language.